Palmitoylethanolamide in Fibromyalgia: Results from Prospective and Retrospective Observational Studies. Issue 2 (December 2015) - Giorno, Rosaria; Skaper, Stephen; Paladini, Antonella; Varrassi, Giustino; Coaccioli, Stefano
Abstract Introduction Fibromyalgia syndrome (FM) is characterized by persistent pain which is often refractory to common analgesic therapies and is particularly disabling. The objective of this study was to evaluate the therapeutic efficacy of duloxetine (DLX) + pregabalin (PGB) in patients suffering from FM and the possible added benefit of the lipid signaling molecule, palmitoylethanolamide (PEA). PEA is well-documented to exert anti-inflammatory, analgesic, and pain-relieving effects at both the preclinical and clinical level. Methods A total of 80 patients were recruited in two steps. The first was a retrospective observational study comprising 45 patients. This patient group received DLX + PGB for 6 months. The second step was a prospective observational study with 35 patients. Patients in this cohort began treatment with DLX + PGB at the same dosage as for the retrospective study plus micronized PEA (PEA-m® ; Epitech Group, Italy) and ultramicronized PEA (PEA-um® ; Epitech Group, Italy) for 3 months. Positive tender points (TPs), pain evoked, and pain intensity were evaluated at baseline and after 3 and 6 months in both studies. Statistical analyses were employed for comparison of data within the two studies and between them. Results The retrospective observational study (DLX + PGB), after 3 months of treatment showed a decrease of positive TPs, pain evoked, and pain intensity. After 6 months of treatment, these parameters had further improvement. In the prospective observational study (DLX + PGB + PEA), PEA introduction after 3 months of therapeutic regimen with DLX + PGB provided a significant improvement in pain symptoms, with a further reduction in the number of TPs and significant reduction in pain, compared to combined DLX + PGB only (p  < 0.0001 for TPs and Visual Analog Scale comparisons). None of the patients experienced adverse side effects. Conclusion Our study confirms the efficacy of DLX + PGB and demonstrates as well the added benefit and safety of PEA in the treatment of pain in patients affected by FM.